Brain oscillations, connectomes and neurophysiology - Liuzzi, Lucrezia (2019)
Magnetoencephalography (MEG) is a neuroimaging technique allowing the investigation of brain function non-invasively, by detecting changes in magnetic fields outside the head induced by ensembles of neurons firing synchronously. Oscillatory electrophysiological activity measured using MEG has been shown to support long range functional communication in the brain, showing close resemblance to known fMRI functional networks. Interest in functional connectivity is growing as disruptions in the functional connectome have been implicated in both neurological and mental health conditions. However, the connection between brain oscillations, functional connectivity and neurochemistry still remains largely unexplored. In this thesis I aim to shed light on this connection.